2011
DOI: 10.1590/s1983-14472011000100021
|View full text |Cite
|
Sign up to set email alerts
|

Escalas de rastreamento para depressão pós-parto: uma revisão sistemática

Abstract: 159Schardosim JM, Heldt E. Escalas de rastreamento para depressão pós-parto: uma revisão sistemática. Rev Gaúcha Enferm., Porto Alegre (RS) 2011 mar;32(1):159-66. ARTIGO DE REVISÃO ESCALAS DE RASTREAMENTO PARA DEPRESSÃO PÓS-PARTO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
4
0
10
Order By: Relevance
“…Ocorre nas primeiras duas semanas após o nascimento do bebê, os sintomas envolvem ansiedade severa, alucinações e delírios; exigem acompanhamento terapêutico e medicamentoso intensivo além de supervisão por conta da possibilidade de suicídio ou agressões ao bebê. (Schardosim & Heldt, 2011;DSM-V, 2013).…”
Section: Resuménunclassified
“…Ocorre nas primeiras duas semanas após o nascimento do bebê, os sintomas envolvem ansiedade severa, alucinações e delírios; exigem acompanhamento terapêutico e medicamentoso intensivo além de supervisão por conta da possibilidade de suicídio ou agressões ao bebê. (Schardosim & Heldt, 2011;DSM-V, 2013).…”
Section: Resuménunclassified
“…They reinforce that the unmarried woman during pregnancy experiences a sense of incapacity for not being able to offer a complete family structure to the baby; As well as, may feel unequal for not being able to share new tasks and/or responsibilities with a partner and/or spouse. They also point out that unmarried, low-educated women who are unemployed or unoccupied, smokers or who drink alcohol are very likely to develop psychological distress during or after pregnancy [9].…”
Section: Resultsmentioning
confidence: 99%
“…These results were similar to the ones found in our study. 18 The scores suggestive of PPD were found in 8.6% of women. This percentage is lower than findings of the PDSS validation study in Brazil with a sample of women from Pernambuco, which results showed 16.7% with scores above the cut-point of 102.…”
Section: Discussionmentioning
confidence: 98%